Representation of people of South Asian origin in cardiovascular outcome trials of glucose‐lowering therapies in Type 2 diabetes. Issue 1 (28th April 2016) - Khunti, K.; Bellary, S.; Karamat, M. A.; Patel, K.; Patel, V.; Jones, A.; Gray, J.; Shepherd, P.; Hanif, W.; ,
Abstract: Aims: Our aim was to investigate the proportional representation of people of South Asian origin in cardiovascular outcome trials of glucose‐lowering drugs or strategies in Type 2 diabetes, noting that these are among the most significant pieces of evidence used to formulate the guidelines on which clinical practice is largely based. Methods: We searched for cardiovascular outcome trials in Type 2 diabetes published before January 2015, and extracted data on the ethnicity of participants. These were compared against expected values for proportional representation of South Asian individuals, based on population data from the USA, from the UK, and globally. Results: Twelve studies met our inclusion criteria and, of these, eight presented a sufficiently detailed breakdown of participant ethnicity to permit numerical analysis. In general, people of South Asian origin were found to be under‐represented in trials compared with UK and global expectations and over‐represented compared with US expectations. Among the eight trials for which South Asian representation could be reliably estimated, seven under‐represented this group relative to the 11.2% of the UK diabetes population estimated to be South Asian, with the representation in these trials ranging from 0.0% to 10.0%. Conclusions: Clinicians should exercise caution when generalizing the results of trials to their own practice, with regard to the ethnicity of individuals. Efforts should be made to improve reporting of ethnicity and improve diversity in trial recruitment, although we acknowledge that there are challenges that must be overcome to make this a reality. What's new?: This appears to be the first time that the representation of people of South Asian origin within major clinical trials in diabetes has been systematically and quantitatively appraised. The findings not only have implications for necessary caution in the broad application of results from major clinical trials, but also point to a need for further improvement in the recording and reporting of ethnicity and in ensuring representative ethnic balance in trial recruitment.